Concurrent shifts in wintering distribution and phenology in migratory swans - Nuijten, Rascha; Wood, Kevin; Rees, Eileen; Nolet, Bart (Zenodo, 2020)
Range shifts and phenological change are two processes by which organisms respond to environmental warming. Understanding the mechanisms that drive these changes is key for optimal conservation and management. Here we study both processes in the migratory Bewick's swan ( Cygnus columbianus bewickii ) using different methods, analysing nearly 50 years of resighting data (1970-2017). In this period the wintering area of the Bewick's swans shifted eastwards ("short-stopping") at a rate of >12.5 km y -1 , thereby shortening individual migration distance on average by 353 km. Concurrently, the time spent at the wintering grounds has reduced ("short-staying") by ~38 days since 1989. We show that individuals are consistent in their migratory timing in winter, indicating that the frequency of individuals with different migratory schedules has changed over time (a generational shift). In contrast, for short-stopping we found evidence for both individual plasticity (individuals decrease their migration distances over their lifetime) and generational shift. Additional analysis of swan resightings with temperature data showed that, throughout the winter, Bewick's swans frequent areas where air temperatures are c. 5.5˚C. These areas have also shifted eastwards over time, hinting that climate warming is a contributing factor behind the observed changes in the swans' distribution. The occurrence of winter short-stopping and short-staying suggests that this species is to some extent able to adjust to climate warming, but benefits or repercussions at other times of the annual cycle need to be assessed. Furthermore, these phenomena could lead to changes in abundance in certain areas, with resulting monitoring and conservation implications. Understanding the processes and driving mechanisms behind population changes therefore is important for population management, both locally and across the species range.